2011
DOI: 10.1111/j.1524-475x.2011.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel, highly quantitative in vivo model for the study of biofilm‐impaired cutaneous wound healing

Abstract: A growing body of evidence suggests that in addition to hypoxia, ischemia-reperfusion injury, and intrinsic host factors, bacterial biofilms represent a fourth major pillar in chronic wound pathogenesis. Given that most studies to date rely on in vitro or observational clinical data, our aim was to develop a novel, quantitative animal model enabling further investigation of the biofilm hypothesis in vivo. Dermal punch wounds were created in New Zealand rabbit ears, and used as uninfected controls, or inoculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
150
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(159 citation statements)
references
References 31 publications
2
150
1
6
Order By: Relevance
“…Virulence factors, including lipopolysaccharide (LPS), enterotoxin A, and ADP ribosylating enzymes excreted by P. aeruginosa have proven to be cytotoxic and have potent inhibitory effects on the proliferation of human granulocytes and macrophage progenitor cells during the wound healing process [36,37]. In vivo studies of mice and rabbits have further confirmed that S. aureus and P. aeruginosa evade host immunity and establish persistent infections via biofilm formation [38][39][40]. When compared to planktonic cells, bacteria in biofilm promote higher resistance towards antibiotics and other antimicrobial agents [6,41].…”
Section: Discussionmentioning
confidence: 91%
“…Virulence factors, including lipopolysaccharide (LPS), enterotoxin A, and ADP ribosylating enzymes excreted by P. aeruginosa have proven to be cytotoxic and have potent inhibitory effects on the proliferation of human granulocytes and macrophage progenitor cells during the wound healing process [36,37]. In vivo studies of mice and rabbits have further confirmed that S. aureus and P. aeruginosa evade host immunity and establish persistent infections via biofilm formation [38][39][40]. When compared to planktonic cells, bacteria in biofilm promote higher resistance towards antibiotics and other antimicrobial agents [6,41].…”
Section: Discussionmentioning
confidence: 91%
“…Outcomes such as impairment of epithelialization, overabundance of granulation tissue, and a hyperinflammatory state are interesting. 8,26,[40][41][42][43] However, reported studies involve short-term infection disallowing prolonged interaction between polymicrobial pathogens and the host. In that respect, the rabbit ear model suffers from limitations comparable to those discussed for the rodent models.…”
Section: In Vivo Biofilm Modelsmentioning
confidence: 99%
“…Moreover, owing to similarities of rabbit ear skin to that of human skin, New Zealand white rabbit ear models have been established for wound healing research. Rabbits are also used to determine inflammatory responses of wounds to bacterial biofilm infection 6, 7, 8 and diabetic neuroischemic wound healing 9.…”
mentioning
confidence: 99%